Level of awareness of high school students in the province of Laguna on the library science profession basis for promotional strategy Jane L. Bebeng ; Vyva Victoria M. Aguirre, adviser ; Herminia H. Santos, reader. - Bebeng, Jane L. (2007)
The shortage in the supply of library science professionals can be attributed to the few graduates of Library and Information Science (LIS) course. In this regard, it is but logical to presume that the course lacks rigorous promotion. In business, a new product or slow selling product needs intensive promotional efforts to make the customers aware of its existence before an eventual purchase would occur. First and foremost, awareness of the target market must be established before any promotion takes place. Thus, acquiring information on the awareness of the prospective college students regarding library science profession is one way of establishing valuable information for devising promotional strategies. These would provide insights to the high school graduating students in order to sway them to enroll in LIS program. It is in this premise that a study to determine the level of awareness of fourth year high school students in the province of Laguna on the library science profession is conducted. This is to generate baseline data required in formulating promotional strategies that are hoped will persuade and attract students to pursue a course in library science.